2022
DOI: 10.1186/s12888-022-03716-6
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances predict active suicidal ideation the next day: an ecological momentary assessment study

Abstract: Background Sleep disturbances are an underestimated risk factor for suicidal ideation and behavior. Previous research provided preliminary support of a temporal relationship between sleep disturbances and suicidal ideation. The present study therefore sought to investigate the prospective association between sleep disturbances, passive and active suicidal ideation, and further psychological risk factors, such as state impulsivity and depression. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Ego depletion research has shown that fatigue ( 72 ) and poor sleep ( 73 ) moderate the relationship between self-control demands and a reduced self-control capacity. Although there is no direct evidence that sleep problems influence an individual’s self-regulatory behavior or diminish their capacity for self-control during a suicidal crisis, recent EMA research has shown that poor sleep quality and short sleep duration were temporally associated with suicidal ideation ( 74 ). Furthermore, an EMA study ( 75 ) with high-risk adolescents has found that shorter-than-usual sleep duration predicted the presence and intensity of next-day suicidal ideation via heightened affective reactivity to negative interpersonal events, a finding in line with the DSMS.…”
Section: New Directions Of Conceptualizing Suicidality: the Dual-syst...mentioning
confidence: 99%
“…Ego depletion research has shown that fatigue ( 72 ) and poor sleep ( 73 ) moderate the relationship between self-control demands and a reduced self-control capacity. Although there is no direct evidence that sleep problems influence an individual’s self-regulatory behavior or diminish their capacity for self-control during a suicidal crisis, recent EMA research has shown that poor sleep quality and short sleep duration were temporally associated with suicidal ideation ( 74 ). Furthermore, an EMA study ( 75 ) with high-risk adolescents has found that shorter-than-usual sleep duration predicted the presence and intensity of next-day suicidal ideation via heightened affective reactivity to negative interpersonal events, a finding in line with the DSMS.…”
Section: New Directions Of Conceptualizing Suicidality: the Dual-syst...mentioning
confidence: 99%
“…As one of the first studies to evaluate these daily and within-person associations in a high-risk sample of youth using subjective and actigraphic methods, our findings also should be replicated in larger samples and among young people with and without depression or suicidal behavior to better understand how, when, and for whom sleep and affective reactivity may be associated with increased proximal risk for SI and behaviors. Although our sample contains over 3,000 days of data collection and is comparable in its sample size to other studies that used intensive Sleep, affective reactivity, and suicidal ideation monitoring designs, including clinical samples (Br€ udern et al, 2022;Czyz et al, 2019;Glenn, Kleiman, Kearns, et al, 2021;Kleiman et al, 2017;Littlewood et al, 2019), the nature of our sample and its relatively small size limit generalizability and the meaningful nature of effects to our samples. Of note, effect sizes for results are not provided in the current study given ongoing debate about the interpretation and meaning of effects at the within-and between-person levels, and caution is advised when interpreting these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Given that both sleep disruption and SI fluctuate across days (Kleiman et al., 2017 ; Littlewood et al., 2019 ), intensive monitoring designs are particularly well‐suited to examine whether changes in sleep within person proximally influence subsequent SI on a daily basis. Recent research using intensive monitoring designs finds that sleep disturbance predicts next‐day active SI (Brüdern et al., 2022 ; Littlewood et al., 2019 ), including self‐reported sleep problems among adolescents following discharge from a psychiatric hospital (Glenn et al., 2022 ). Despite these advancements, our understanding of the potential mechanisms through which sleep and SI are linked in adolescents and young adults remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Drawing from empirical studies showing that disruptions in sleep (eg, [ 35 , 36 ]) and increases in substance abuse (eg, [ 37 ]) are related to increased suicidal thoughts and behaviors, we hypothesize that:…”
Section: Introductionmentioning
confidence: 99%